Faktor Predisposisi Yang Berhubungan Dengan Pemilihan Metode Kontrasepsi Jangka Panjang (MKJP) Pada Wanita Usia Subur (WUS) Di Puskesmas Binong Tahun 2023 - Hilwa Syahidah; Rini Handayani; Erna Veronika; Ade Heryana (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
One of the government's efforts to reduce the population growth rate in Indonesia is the Family Planning Program. The Indonesian government recommends the Long-Term Contraceptive Method as it is mentioned as one of the targeted outcomes in Indonesia's Medium-Term National Development Plan 2020-2024 (28% by 2024). The number of MKJP acceptors at Binong Health Center has decreased in the last 3 years. In 2021 it is 7.6%, in 2022 it is 6.8%, and in 2023 until November 2023 it is 5%. This indicates that the interest of MKJP at the Binong Health Center is still very low compared to non-MKJP. This research was conducted to determine the predisposing factors associated with the selection of long contraceptive methods at Binong Health Center in 2023. The type of research is quantitative research with a case-control study design with a ratio of 1: 1, consisting of 62 case groups and 62 control groups. This study used Simple Random Sampling technique. This research was conducted using secondary data through medical document review. Data analysis was performed using the chi-square test. The results of the bivariate analysis showed that variables related to the selection of MKJP at Binong Health Center are occupation (p-value = 0.029) and the number of children (p-value = 0.007), while the unrelated variables with the election of MKJP at the Binong Health Center are age (p-value = 0.189) and education (p-value = 0.082). It is expected that further research will be conducted at the Binong Health Center related to factors that affect the use of MKJP with different variables that are likely to influence more such as perception, attitude, side effects. knowledge and exposure to information.